2017
DOI: 10.1007/978-1-4939-6934-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Biology in Cancer

Abstract: Cells depend on the lysosome for sequestration and degradation of macromolecules in order to maintain metabolic homeostasis. These membrane-enclosed organelles can receive intracellular and extracellular cargo through endocytosis, phagocytosis, and autophagy. Lysosomes establish acidic environments to activate enzymes that are able to break down biomolecules engulfed through these various pathways. Recent advances in methods to study the lysosome have allowed the discovery of extended roles for the lysosome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 128 publications
(120 reference statements)
1
68
0
1
Order By: Relevance
“…Movement of lysosomes towards the cell periphery is also observed in cancer cell lines and is required for cancer invasion, migration, and metastasis [24,44]. In this case, lysosomal exocytosis occurs, leading to the secretion of acidic hydrolases and metalloproteinases that are required for degradation of the extracellular matrix to promote metastasis of cancer cells [45,46]. Recently, inhibition of AC was found to cause suppression of the interaction between lysosomes and the multivesicular body, and hence the increase of exosome release from podocytes, highlighting the role of AC in TRPML1 channel-mediated Ca 2+ release [47].…”
Section: Discussionmentioning
confidence: 99%
“…Movement of lysosomes towards the cell periphery is also observed in cancer cell lines and is required for cancer invasion, migration, and metastasis [24,44]. In this case, lysosomal exocytosis occurs, leading to the secretion of acidic hydrolases and metalloproteinases that are required for degradation of the extracellular matrix to promote metastasis of cancer cells [45,46]. Recently, inhibition of AC was found to cause suppression of the interaction between lysosomes and the multivesicular body, and hence the increase of exosome release from podocytes, highlighting the role of AC in TRPML1 channel-mediated Ca 2+ release [47].…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes recycle organelles and proteins in cells [50] and they play extensive roles in various diseases, including cancers, making them an attractive and targetable node for therapeutic intervention. In liver cancer, lysosomes are known to be involved in the chemoresistance of HCC cells [51,52]. Here, we used LysoTracker probes to assess the lysosomal contents of cells and found that FAM215A had a positive effect on the lysosomal content of HCC cells.…”
Section: Discussionmentioning
confidence: 91%
“…An acidic environment is necessary for autophagosome–lysosome fusion in mammalian cells. An increasing pH has the same inhibitory effect on the fusion process as the anti‐autophagic macrolide bafilomycin A1, although the latter cannot inhibit the fusion process resulting in amphisome formation (Kawai et al , ; Klionsky et al , ; Fennelly & Amaravadi, ).…”
Section: Convergence Of Autophagy and Endocytosismentioning
confidence: 99%